Envisioning a Transdisciplinary University. Issue 2 (December 2014) - Carroll, Leigh; Ali, Mohammed K.; Cuff, Patricia; Huffman, Mark D.; Kelly, Bridget B.; Kishore, Sandeep P.; Narayan, K. M. Venkat; Siegel, Karen R.; Vedanthan, Rajesh
<x xml:space="preserve">Abstract</x> Achieving social and economic growth requires collaboration, especially in global health. If universities are to improve health globally, they will need to train students and to support faculty who can effectively collaborate with those from other disciplines and cultures.